Improving farmers' access to clean planting material through partnership in the value chain. - Ndirigwe, J.; Sindi, K.; Kankundiye, L.; Shumbusha, D.; Nshimiye, J.C.; Hakizimana, S.; Low, Jan W. (2012)
Sweetpotato is an important food security crop in Rwanda grown mainly by women for household consumption and as a source of family income Sweetpotato production is faced with several constraints, among them the availability of clean planting of most varieties but more so of the new Vitamin A richOrange Fleshed Sweetpotato. This is limiting their potential to benefits producers, processors, and consumers as a source of food based vitamin A. Therefore an efficient sustainable seed system for multiplication and distribution of cleaning planting material to users is vital. Through a thorough need assessment, four districts were identified for OFSP promotion. Farmer based approach was used to develop an effective, rapid and sustainable chain for multiplication and to disseminate clean basic sweetpotato planting material from in vitro lab to subsequent multiplication sites. Public, research, private, development organization, and farmer group's partnership was paramount to clean, multiply, identify, organize and train farmers' groups in different modules. Most of the new varieties namely, Cacearpedo, Gihingamukungu, and Ukerewe possess preferred traits by farmers compared to their local ones. Now farmers know the importance of using clean planting cuttings as a factor to increase productivity when planted at right time. Initial comparison of harvest from two consecutive seasons, May to July 2011 and July to December 2011 the study finds an increase of yield of 27% for Cacearpedo, 22% for Ukerewe and 71% for 97-062. This can be attributed to improved technical support, adoption of better agriculture techniques, healthy vines, and on time vines availability.